Detection of Chlamydia trachomatis infections in women by Amplicor PCR: comparison of diagnostic performance with urine and cervical specimens. - Pasternack, R (1996)
We used the Roche Amplicor PCR assay to compare urine and cervical swabs as sample material in the detection of Chlamydia trachomatis causing genital infections. The diagnostic performance of Amplicor PCR was compared with that of cell culture and the Gen-Probe PACE 2 assay with cervical specimens. If discrepant from other results, the specimens negative by PCR were diluted and reanalyzed to reveal PCR inhibitors. Of 666 patients, 39 (5.9%) were confirmed to have chlamydial infection. The respective sensitivity and specificity of Amplicor PCR were as follows: urine specimens, 82.0 and 99.7%; cervical specimens, 82.0 and 99.8%. Those for cell culture with cervical specimens were 84.6 and 100%. For the Gen-Probe PACE 2 assay, the sensitivity and specificity with cervical specimens were 79.5 and 100%, respectively. Without the effect of PCR inhibitors, the sensitivity of PCR with urine would have been 97.4%. Provided that the problems currently caused by inhibitors will be solved, the Amplicor PCR assay with urine specimens offers a tempting alternative for the diagnosis of C. trachomatis infection in women.